2016
DOI: 10.1371/journal.pbio.1002562
|View full text |Cite
|
Sign up to set email alerts
|

EDA-Fibronectin Originating from Osteoblasts Inhibits the Immune Response against Cancer

Abstract: Osteoblasts lining the inner surface of bone support hematopoietic stem cell differentiation by virtue of proximity to the bone marrow. The osteoblasts also modify their own differentiation by producing various isoforms of fibronectin (FN). Despite evidence for immune regulation by osteoblasts, there is limited knowledge of how osteoblasts modulate cells of the immune system. Here, we show that extra domain A (EDA)-FN produced by osteoblasts increases arginase production in myeloid-derived cells, and we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…In a more recent study, ED-A fibronectin was shown to increase the population of myeloid derived cells, known to impair immune responses to cancer cells, from osteoblasts 21. To determine whether the absence of fibronectin impaired myeloid cell numbers and thus tumor formation, the authors subcutaneously injected melanoma cells into either a fibronectin knock out model (cKO) in which fibronectin expression in differentiating osteoblasts was conditionally deleted or a wild type animal (WT) and evaluated for tumor formation 21. Tumor growth and the presence of myeloid cells in tumors were reduced in cKO animals but not in WT animals 21.…”
Section: Tumor Progressionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a more recent study, ED-A fibronectin was shown to increase the population of myeloid derived cells, known to impair immune responses to cancer cells, from osteoblasts 21. To determine whether the absence of fibronectin impaired myeloid cell numbers and thus tumor formation, the authors subcutaneously injected melanoma cells into either a fibronectin knock out model (cKO) in which fibronectin expression in differentiating osteoblasts was conditionally deleted or a wild type animal (WT) and evaluated for tumor formation 21. Tumor growth and the presence of myeloid cells in tumors were reduced in cKO animals but not in WT animals 21.…”
Section: Tumor Progressionmentioning
confidence: 96%
“…Tumor growth and the presence of myeloid cells in tumors were reduced in cKO animals but not in WT animals 21. Although the authors don't attribute these findings to a specific reduction in the ED-A fibronectin isoform, they go on to demonstrate that culture of myeloid cells from cKO animals with ED-A fibronectin resulted in a reduction of melanoma apoptosis, suggesting that this pro-tumor effect results from ED-A activation of myeloid cells 21.…”
Section: Tumor Progressionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our data suggest that this aberrant repair in the aged lung is facilitated by fibronectin EDA, which is not only increased in the aging lung, but also increased in the aging lung in response to bleomycin, when compared to young lungs. It is important to note that these mechanisms may vary in different cancers as aging does not appear to affect tumor progression similarly when different tumors are tested [130].…”
Section: Discussionmentioning
confidence: 99%